Risiko Operasional Layanan Digital BYOND terhadap Kepuasan Nasabah BSI - Putri Cahyaningtyas; Zakiatun Nufus; Yani Aguspriani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the effect of BYOND digital service operational risks on Bank Syariah Indonesia customer satisfaction. The research method used is a quantitative approach with a causal associative design. Data were collected through a Likert scale-based questionnaire distributed online to students of the 2023 Sharia Banking Study Program at UIN Sultan Maulana Hasanuddin Banten, with a total of 66 respondents. Data analysis techniques used simple linear regression and t-tests with the help of SPSS version 25. The results showed that the operational risk of BYOND digital services had a positive and significant effect on customer satisfaction, with a regression coefficient value of 0.507 and a significance value of 0.001 < 0.05. The coefficient of determination (R²) value of 0.152 indicates that operational risk can explain 15.2% of the variation in customer satisfaction. This study emphasizes the importance of managing the operational risk of digital services in improving customer satisfaction in Islamic banking.